2021
DOI: 10.1111/1462-2920.15687
|View full text |Cite
|
Sign up to set email alerts
|

Facing the wrath of enigmatic mutations: a review on the emergence of severe acute respiratory syndrome coronavirus 2 variants amid coronavirus disease‐19 pandemic

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an emerging respiratory virus responsible for the ongoing coronavirus disease 19 (COVID-19) pandemic. More than a year into this pandemic, the COVID-19 fatigue is still escalating and takes hold of the entire world population. Driven by the ongoing geographical expansion and upcoming mutations, the COVID-19 pandemic has taken a new shape in the form of emerging SARS-CoV-2 variants. These mutations in the viral spike (S) protein enhance the vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 91 publications
0
27
0
Order By: Relevance
“…Clinical research showed that the emergence of the Delta variant can incite damage in the lung, liver, gastrointestinal system, vascular, neurological system, heart, pancreas, kidneys and other organs of infected people, leading to a series of clinical manifestations, such as cough, pneumonia, dyspnea, acute respiratory distress syndrome (ARDS), respiratory failure, liver damage, abdominal pain, disseminated intravascular coagulation (DIC), myocardial damage, pancreatic injury and acute kidney injury as other SARS-CoV-2 variants (Figure 2) [28,29]. In particular, the Delta variant also displays a series of unique physiological characteristics and clinical features compared to other SARS-CoV-2 variants, such as high viral load, strong transmissibility and resistance against existing monoclonal antibodies therapy [30][31][32][33][34]. These features of the Delta Variant have led to higher transmission characteristics and mortality compared with other SARS-COV-2 variants.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical research showed that the emergence of the Delta variant can incite damage in the lung, liver, gastrointestinal system, vascular, neurological system, heart, pancreas, kidneys and other organs of infected people, leading to a series of clinical manifestations, such as cough, pneumonia, dyspnea, acute respiratory distress syndrome (ARDS), respiratory failure, liver damage, abdominal pain, disseminated intravascular coagulation (DIC), myocardial damage, pancreatic injury and acute kidney injury as other SARS-CoV-2 variants (Figure 2) [28,29]. In particular, the Delta variant also displays a series of unique physiological characteristics and clinical features compared to other SARS-CoV-2 variants, such as high viral load, strong transmissibility and resistance against existing monoclonal antibodies therapy [30][31][32][33][34]. These features of the Delta Variant have led to higher transmission characteristics and mortality compared with other SARS-COV-2 variants.…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 is an enveloped virus displaying characteristic crown-like projections on its surface. Structurally, the virus codes for four structural proteins, namely the Envelope (E), Membrane (M), Spike (S), and Nucleocapsid (N) proteins [3]. These proteins cumulatively aid viral entry into host cells, subsequent infection, replication, and assembly of virion particles.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its highly mutative positive-sense ssRNA genome, infection cycle, and the expansion of viral geographical range, variants of SARS-CoV-2 have also emerged during this pandemic [3]. This makes the present situation more intense, making the epidemiologists and researchers reiterate their line of action before the mutants unleash a wave of violent infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic has presented the urgent need for governments, healthcare decision makers, providers, and others, to refocus on balancing their response with wider health needs. The increased availability of novel web-based data sources can substantially improve infectious disease surveillance (Choi et al, 2016;Ainsworth et al, 2021). Globally, web-based surveillance tools and epidemic intelligence methods are providing new prospects to facilitate risk assessment and timely outbreak detection.…”
Section: Introductionmentioning
confidence: 99%